Diffuse noxious inhibitory controls and nerve injury: restoring an imbalance between descending monoamine inhibitions and facilitations. Issue 9 (September 2015) - Bannister, Kirsty; Patel, Ryan; Goncalves, Leonor; Townson, Louisa; Dickenson, Anthony H.
Abstract : Abstract: Diffuse noxious inhibitory controls (DNICs) utilize descending inhibitory controls through poorly understood brain stem pathways. The human counterpart, conditioned pain modulation, is reduced in patients with neuropathy aligned with animal data showing a loss of descending inhibitory noradrenaline controls together with a gain of 5-HT3 receptor-mediated facilitations after neuropathy. We investigated the pharmacological basis of DNIC and whether it can be restored after neuropathy. Deep dorsal horn neurons were activated by von Frey filaments applied to the hind paw, and DNIC was induced by a pinch applied to the ear in isoflurane-anaesthetized animals. Spinal nerve ligation was the model of neuropathy. Diffuse noxious inhibitory control was present in control rats but abolished after neuropathy. α2 adrenoceptor mechanisms underlie DNIC because the antagonists, yohimbine and atipamezole, markedly attenuated this descending inhibition. We restored DNIC in spinal nerve ligated animals by blocking 5-HT3 descending facilitations with the antagonist ondansetron or by enhancing norepinephrine modulation through the use of reboxetine (a norepinephrine reuptake inhibitor, NRI) or tapentadol (μ-opioid receptor agonist and NRI). Additionally, ondansetron enhanced DNIC in normal animals. Diffuse noxious inhibitory controls are reduced after peripheral nerve injury illustrating the central impact of neuropathy, leading to an imbalance in descending excitations and inhibitions. Underlying noradrenergic mechanisms explain the relationship between conditioned pain modulation and the use of tapentadol and duloxetine (a serotonin, NRI) in patients. We suggest that pharmacological strategies through manipulation of the monoamine system could be used to enhance DNIC in patients by blocking descending facilitations with ondansetron or enhancing norepinephrine inhibitions, so possibly reducing chronic pain. Abstract : Diffuse noxious inhibitory controls (DNICs) are reduced after neuropathy. α2 adrenoceptor- and 5-HT3 receptor-mediated mechanisms underlie DNIC because drugs that modulate these receptors restore DNIC-mediated inhibition after neuropathy.